Role of collapsin response mediator proteins in optic nerve injury - ZHU Yuchun, XI Xinyuan, YANG Zhen, FENG Dongfu (Jichu yixue yu linchuang)
Collapsin response mediator proteins (CRMPs), also known as dihydropyrimidine-like proteins, contain five isoforms (CRMP1, CRMP2, CRMP3, CRMP4, CRMP5). In central nervous system, CRMPs are mainly involved in a variety of physiological processes such as neuronal differentiation and migration, synaptic plasticity, neurite growth and development and guiding extension. Recent studies have found that inhibiting or reducing the phosphorylation of CRMPs can affect the survival and axonal regeneration of retinal ganglion cells (RGCs) after optic nerve injury, which may provide new ideas for the treatment of optic nerve injury in the future.